Glischrochilus (Librodor) forcipatus (Fairmaire, 1889) rediscovered (Coleoptera: Nitidulidae) - Jelínek, Josef; Lasoń, Andrzej; Hájek, Jiří (Zootaxa, 2012)
Glischrochilus (Librodor) forcipatus (Fairmaire, 1889) has been known from the single holotype which could not be dissected, so that the status of the species remained doubtful. New specimens of G. forcipatus, recently collected after ca. 120 years, are redescribed and compared with related species G. (L.) japonius (Motschulsky, 1857), G. (L.) jelineki Lasoń, 2009 and G. (L.) parvipustulatus (Kolbe, 1886). Validity of G. forcipatus is confirmed and key for identification of the similar species is given.